A297 GOBLET CELLS AND INTESTINAL TREFOIL FACTOR PLAY CRITICAL ROLES IN INNATE PROTECTION AGAINST CLOSTRIDIUM DIFFICILT COLITIS AND MEDIATE RECOVERY FOLLOWING CDIF COLITIS. (1st March 2018) - Tang, H; Nguyen, J; Li, Y; MacDonald, J A; Beck, P
Abstract: Background: Cdif colitis is a leading cause of morbidity and mortality in many populations including elderly hospitalized, those with inflammatory bowel disease, and the immunosuppressed. Although depletion of the density and diversity of the intestinal microbiome is clearly the main underlying mechanistic risk factor, little is known of the innate mechanisms involved in protection against Cdif and those involved in recovery following Cdif colitis. One of the hallmarks of Cdif colitis are pseudomembranes (composed of mucus, fibrin and debris). Altered mucus secretion (MUC2) has been described in pts with Cdif colitis. Aims: The hypothesis of the present study was to assess the role of goblet cells, mucins and associated growth factors (ITF, secreted by goblets cells) in mediating protection against Cdif induced injury/inflammation and recovery following Cdif colitis. Methods: Colitis was induced in C57Bl6 mice either via intrarectal administration of Cdif toxin (A&B) or in the Cdif oral gavage infection model. Human tissue models included; in vitro (CaCO2, IECs) & ex vivo studies (fresh human colonic biopsies exposed to toxin A/B). Cdif injury/inflammation was assessed via histology, MPO, cytokine release, permeability, LDH release, apoptosis markers. ITF, MUC2, KGF and goblet cells were assessed via WB, PCR, AB/PAS + immunostaining. Results: Cdif toxin and infection significantly depleted goblet cells, the protective growth factor ITF and MUC2 in mouse and human tissues. Recovery from Cdif colitis was associated with increased ITF expression, MUC2 and goblet cell number. MUC2 -/- mice were more susceptible to Cdif colitis vs wt mice (increased MPO, histological scores). ITF -/- mice had similar levels of acute Cdif colitis but had marked impairment in recovery from colitis at 24 and 48h post toxin exposure. We then assessed the role of keratinocyte growth factor (KGF) which is upstream of ITF and induces ITF expression. KGF -/- mice had decreased ITF and increased toxin induced goblet cell depletion and markedly impaired recovery from Cdif colitis. Exogenous KGF (i.p.) enhanced recovery from Cdif colitis in wt and KGF-/- mice but not in ITF-/- mice. In our human tissue models ITF or KGF exposure reduced Cdif toxin induced injury (barrier function, LDH release, apoptosis and cytokine release). Conclusions: Goblet cells, MUC2 and growth factors ITF and KGF are important in the innate protection against Cdif colitis and are critical in the recovery from Cdif colitis. These findings mat lead to new approached in the management of patients with Cdif coltis. Funding Agencies: CIHR